The right to food in Mozambique : a conceptual critique on the applicability of the UN Convention on Economic Social and Cultural Rights - Hansungule, Michelo (University of Pretoria, 2019)
Mini Dissertation (MPhil)--Universiity of Pretoria, 2019.